Developing a pedagogical evaluation framework for computational thinking supporting technologies and tools - Oyelere, Solomon Sunday; Agbo, Friday Joseph; Sanusi, Ismaila Temitayo (Frontiers in Education, 2022)
Frameworks for the evaluation of technological instructional tools provide educators with criteria to assess the pedagogical suitability and effectiveness of those tools to address learners’ needs, support teachers’ understanding of learning progress and recognize the levels of achievement and the learning outcomes of the students. This study applied secondary document analysis and case study to identify five pedagogical indicators for teaching and learning computational thinking, including technology, pedagogical approaches, assessment techniques, data aspect, and teacher professional development. Based on the pedagogical indicators, this study proposed a computational thinking pedagogical assessment framework (CT-PAF) aimed at supporting educators with a strategy to assess the different technological learning tools in terms of pedagogical impact and outcome. Furthermore, three case-study instructional tools for teaching computational thinking in K-12 were analyzed for the initial assessment of CT-PAF. Scratch, Google Teachable Machine, and iThinkSmart minigames were marched to the underpinning characteristics and attributes of CT-PAF to evaluate the framework across the instructional tools. The initial assessment of CT-PAF indicates that the framework is suitable for the intended purpose of evaluating technological instructional tools for pedagogical impact and outcome. A need for expanded assessment is, therefore, necessary to further ascertain the relevance of the framework in other cases.